Clear Cell Chondrosarcoma: Clinical Characteristics and Outcomes in 15 Patients. (30th December 2020) - Flint, James H.; Conley, Anthony P.; Rubin, M. Laura; Feng, Lei; Lin, Patrick P.; Moon, Bryan; Bird, Justin; Satcher, Robert L.; Lewis, Valerae O.
Abstract : Background . Clear cell chondrosarcoma (CCC) represents less than 6% of all chondrosarcomas, and thus, our understanding of this rare entity is limited. Analyzing clinical characteristics and treatment patterns, thus increasing our knowledge, may improve treatment strategy. We review our institutional experience with 15 patients, including one case with dedifferentiation. Methods . A retrospective review was conducted in CCC patients treated at our institution from 1996 to 2015, with at least 2-year follow-up. Descriptive statistics and Kaplan–Meier survival analyses were performed. Results . Of 19 patients identified, 15 patients had at least 2-year follow-up and were included. The median age at diagnosis was 43 years. 80% were male. The most common presenting signs were pain (12 patients; 80%) and fracture (2 patients; 13.3%). The most common site was proximal femur (8 patients; 53%). All patients had MSTS Stage I disease. Primary treatment included wide resection in 10 patients (67%) and intralesional or marginal resection in 5 patients (33%). Three patients died of disease during the study period, 1 with dedifferentiation of recurrent CCC. The median time to death from disease was 15.3 years (95% CI: (14.2; NA)). The median time to either recurrence or death was 7.73 years for patients who had intralesional/marginal resection and 16.44 years for patients with wide resection (HR (wide vs. intralesional/marginal) = 0.21, 95% CI: (0.04; 1.18), p = 0.053 ). The median time to recurrence or death was significantly shorter for patients not initially treated at a sarcoma center (p = 0.01 ). Conclusions . CCC is a rare entity, and our understanding of it is still evolving. We observed a higher recurrence rate for intralesional or marginal resection, and wide resection alone remains the mainstay of treatment. Better outcomes were observed in patients initially treated by trained musculoskeletal oncologists. Due to the propensity of CCC to recur decades after initial resection, lifelong surveillance is recommended.